2007
DOI: 10.4012/dmj.26.474
|View full text |Cite
|
Sign up to set email alerts
|

Priming Effects of Triethylene Glycol and Triethylene Glycol Monomethacrylate on Dentin Bonding

Abstract: The objective of this study was to evaluate the effects of triethylene glycol (TEG) and triethylene glycol monomethacrylate (TEGMA) solutions as dentin primers on dentin bonding. To this end, wall-to-wall polymerization contraction gap width of a resin composite in a cylindrical dentin cavity and shear bond strength to a flat dentin surface were measured. Dentin was pretreated with an experimental dentin bonding system -consisting of 0.5 M ethylenediaminetetraacetic acid conditioner, TEG or TEGMA primer, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This was probably because water movement was prevented by triethylene glycol (TEG) which has a similar molecular weight as GM 13) . They also reported that TEG prevented infiltration of the bonding monomers into the branches of the dentinal tubules.…”
Section: Discussionmentioning
confidence: 99%
“…This was probably because water movement was prevented by triethylene glycol (TEG) which has a similar molecular weight as GM 13) . They also reported that TEG prevented infiltration of the bonding monomers into the branches of the dentinal tubules.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we developed experimental dentin primers which completely prevented contraction gap formation of the resin composite. These newly developed dentin primers had the same chemical structure, etherified methacrylate with polyvalent alcohol, that may have an advantage of forming hydro-gel 15,16,19,20) . It was thought that dentin primer altered the physical characteristics of the dentin surface and thus improved dentin bonding.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized that polyethylene glycol methacrylate (PEG) possibly reduced water contamination 14) . Based on this mechanism, we developed an experimental dentin primer composed of aqueous solution of glycecryl monomethacrylate (GM) 15) and tri-ethylene glycol monomethacrylate (TEGMA) 16) , which completely prevented contraction gap formation of light-activated resin composite in a dentin cavity. Thus, it was suggested that the GM primer altered the physical and chemical conditions of the substrate dentin surface, giving it the appearance of an acid-etched enamel surface.…”
Section: Introductionmentioning
confidence: 99%
“…On contraction gap formation, both triethylene glycol (TEG) and triethylene glycol monomethacrylate (TEGMA) have been shown to be highly effective dentin primers because they completely prevented contraction gap formation by virtue of their "pegylation" effect 9) . Likewise, contraction gap formation was completely prevented with GM priming -a result applicable for both sclerotic and sound dentin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we reported that complete marginal integrity was achieved by dentin priming with an aqueous solution of erythritol monomethacrylate, xylitol monomethacrylate, ethylene glycol, 1,6-hexanediol, triethylene glycol, and triethylene glycol monomethacrylate [5][6][7][8][9] . In several studies, the dentin priming effect was investigated by expanding the dentin collagen network which was exposed as a result of decalcification during dentin conditioning and which collapsed as a result of air-drying [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%